Case-Based Decision Support for Disaster Management - Möhrle, Stella (KIT Scientific Publishing, 2020)
Disasters are characterized by severe disruptions of the society's functionality and adverse impacts on humans, the environment, and economy that cannot be coped with by society using its own resources. This work presents a decision support method that identifies appropriate measures for protecting the public in the course of a nuclear accident. The method particularly considers the issue of uncertainty in decision-making as well as the structured integration of experience and expert knowledge.